CYBER TRUST AND CORPORATE REPUTATION: THE ROLE OF IT EXPERT BOARDS - Tabah Rizki; Muhammad Arsalan Khan; Triyono; Arina Hidayati (International Journal of Contemporary Accounting, 2025)
This study aims to examine the effect of cybersecurity disclosure on corporate reputation, with IT expertise on the board of directors as a moderating variable, in the Indonesian banking sector listed on the Indonesia Stock Exchange (IDX) during the 2017–2024 period. This research employs a quantitative descriptive approach using secondary data obtained from sustainability reports and annual reports sourced from the official IDX website and the Thomson Reuters database. The research sample consists of 144 firm-year observations of banking companies. Data were analyzed using panel data regression, with the fixed effects model identified as the most appropriate specification. The results indicate that cybersecurity disclosure has a positive and significant effect on corporate reputation. Furthermore, the presence of IT expertise on the board strengthens this relationship by enhancing signal credibility and the effectiveness of digital governance. From a practical perspective, the findings confirm that board-level IT expertise plays a crucial role in strengthening transparency, public trust, and corporate reputation resilience in the era of digital transformation. The implications of this study suggest that firms should pay greater attention to the quality of cybersecurity disclosures and enhance technological capabilities at the board level to address increasing digital risks. Moreover, these findings may serve as a reference for regulators and stakeholders in formulating more effective cyber governance policies in the financial sector. This study also contributes to the growing literature on cyber governance in emerging markets, particularly Indonesia.